The Role of K-Ras and P53 in Biliary Tract Carcinoma - Saara Ahmad; Bisma Badr; Asra Khan; Rehana Rehman; Kulsoom Ghias; Jibran Sualeh Muhammad; Muhammad Rizwan Khan (Journal of the Pakistan Medical Association, 2021)
Objective: Biliary tract cancers are among the most fatal subtypes of gastrointestinal cancer. The pathogenesis of these tumors involves several molecular alterations in the genes. This review article focuses mainly on the role of K-Ras (a proto-oncogene) and p53 (a tumor-suppressor gene) which are among the most commonly mutated genes, with K-Ras activation being detected in 50% to 75% and P53 inactivation in 30% to 40% of biliary tract carcinomas. Methods: PubMed and Google Scholar were searched using the terms TP53, KRAS, mutation, biliary tract carcinoma, cholangiocarcinoma, murine model. In total, 72 articles were reviewed of which 26 articles from the 21st Century were included in this review. The articles excluded were mere repetitions, duplicates or were irrelevant. No data was retrieved from posters, presentations, cell lines and symposiums. Moreover, experiments involving bile aspirations were not included in this review article. Results: Three studies conducted in China, Japan and Taiwan reported a positive correlation between K-Ras mutation and biliary tract carcinoma. Only one study conducted in China showed the sole correlation between p53 inactivation and biliary tract carcinoma. Among the studies conducted in China, Japan and Europe, only four showed a positive association between both K-Ras mutation and p53 inactivation and biliary tract carcinoma. Conclusion: K-Ras and p53 mutation both contribute to biliary tract carcinoma. K-Ras mutation, however, has a much higher frequency as compared to p53 inactivation in these cancers. Keywords: p53, K-Ras, mutation, biliary tract carcinoma, cholangiocarcinoma, murine models. Continuous..